Evaluation of Women Cases Applied To The ElaziĞ Forensic Medicine Unit Due To Violence By Their Husbands - Tokdemir, Mehmet; Deveci, S. Erhan; Açık, Yasemin (Fırat University, 2003)
Aim: In this study, we aimed to evaluate the various kinds and frequency of violence and the socio-demographic properties of a group of women who have been subjected to physical violence. Material and method: A face to face questionnaire was applied to 44 women who have been subjected to physical violence by their husbands and have been sent to Directorate of Forensic Medicine Department for taking final report in Elazığ center in year 2002. Results: 65.9% of the women subject to violence were at age of 25-45. The education level of 77.3% women subject to violence and 63.6% of the husbands practising violence were graduate of primary education and below. 54.5% of the women were experiencing violence at least 1-2 times a week. Besides physical violence 84.4% were subject to verbal, 31.8% to sexual violence. 52.3% of the women have stated that their husbands use alcohol. There was no significant relation between the alcoholic condition of the men and their sexual violence applied to the women. Despite the violence they experienced 27.3% of the women said that they would continue their marriage because of their children and 13.6% because of economical reasons because they have no social security. Again 34.1% think about leaving their husbands. 93.2% of the women have received habitual occupation the period of inability reports for a period of 10 days or less and 6.8% for 11-20 days. Conclusion: Physical violence is accompanied mostly by verbal and sexual violence. However, the women continue their marriages despite the violence they experience because of their children or because of economical reasons having no social security.

Amaç: Bu araştırmada, fiziksel şiddet mağduru bir grup kadının sosyo-demografik özelliklerinin, gördükleri diğer şiddet türlerinin ve sıklığının değerlendirilmesi amaçlanmıştır. Gereç ve yöntem: Elazığ il merkezinde 2002 yılında eşi tarafından uygulanan fiziksel şiddete maruz kalarak, Adli Tıp Şube Müdürlüğü'ne kati rapor almak için gönderilen 44 kadına yüz yüze görüşülerek anket uygulanmıştır. Bulgular: Şiddet mağduru kadınların %65.9'u 25-45 yaşları arasındadır. Fiziksel şiddete maruz kalan kadınların %77.3'ünün, uygulayan erkeklerin ise %63.6'sının eğitim düzeyi ilköğretim mezunu ve altıdır. Kadınların %54.5'i haftada en az 1-2 kez fiziksel şiddet görmektedir. Fiziksel şiddet yanı sıra %86.4'ü eşleri tarafından uygulanan sözel, %31.8'i ise cinsel şiddete maruz kalmaktadır. Kadınların %52.3'ü eşinin alkol kullandığını belirtmiştir. Erkeklerin alkol kullanma durumu ile eşlerine karşı uyguladıkları cinsel şiddet arasında anlamlı bir ilişki yoktur. Gördükleri şiddete rağmen, kadınların %27.3'ü çocukları için, %13.6'sı sosyal güvencesi olmadığından ekonomik nedenlerden dolayı evliliğini sürdürdüğünü belirtmiştir. Yine %34.1'i eşinden ayrılmayı düşünmektedir. Kadınların adli raporlarında; %93.2'sine 10 gün veya daha az, %6.8'ine ise 11-20 gün süreyle mutat iştigale engel süreleri verilmiştir. Sonuç: Fiziksel şiddet çoğunlukla sözel ve cinsel şiddeti de beraberinde getirmektedir. Ancak kadınlar, gördükleri şiddete rağmen çocukları için ya da sosyal güvencesi olmadığından ekonomik nedenlerden dolayı evliliklerini sürdürmektedir.
Elazığ Adli Tıp Şube Müdürlüğüne Eşi Tarafından Şiddete Maruz Kalma Nedeniyle Başvuran Kadınların Değerlendirilmesi